Analisis Overlay Potensi Pendapatan Asli Daerah Sebagai Salah Satu Sumber Pendapatan Daerah di Kabupaten Lombok Tengah Tahun 2013-2022 - Muhammad Alif Bimanday; Muaidy Yasin; Endang Astuti (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study is entitled Overlay analysis of regional original revenue potential as one of the sources of regional revenue in Central Lombok regency in 2013-2022 with the aim of analyzing the potential of regional original revenue of Central Lombok regency in 2013-2022 with several steps (1) analyzing PAD construction of Central Lombok regency in 2013-2022, (2) analyzing PAD growth of Central Lombok regency in 2013-2022, and (3) analyzing PAD potential of Central Lombok regency in 2013-2022 by calculating the yield of contributions and growth. This study uses a quantitative approach with descriptive methods. This study was conducted in Central Lombok Regency at the regional Revenue Agency (BAPENDA). The method of data analysis used in this study is Overlay analysis. The results of this study are (1) pad contribution analysis of Central Lombok regency in 2013-2022 obtained an average result of 10.10% with unfavorable criteria, (2) PAD growth analysis of Central Lombok regency in 2013-2022 obtained an average result of 16.96%. (3) Overlay PAD analysis of Central Lombok regency in 2013-2022 obtained an average contribution of 0.99 (low) and an average growth of 1.00 (high) with potential criteria.